Traditional Siddha Medicinal Herbs Used in the Treatment Urinary Tract Infection (Muthira Kiricharam)- A Narrative Review - Sivaranjani Kumarasamy,; Meera Radhakrishnan, (International Journal of Ayurveda and Pharma Research, 2022)
Urinary tract infection is one the commonest bacterial infection in clinical practice. The infection mostly occurs in the lower part of urinary tract i.e., urinary bladder and urethra in which women are commonly affected due to the anatomical variation in urethra. UTI are primarily caused by gram-negative bacteria, but gram-positive bacteria may also be involved. The most common pathogen is Escherichia coli with the frequency rate of 33%, followed by Klebsiella pneumoniae (11%), Staphylococcus aureus (22.2%), Pseudomonas sp. (7.4%). UTI is commonly represented with the symptoms related to cystitis and pyelonephritis such as dysuria (painful urination), increased frequency of urine, supra pubic discomfort and pain in flanks, etc. As per Siddha text, UTI can be correlated with the terms Muthira kiricharam which has other synonyms such as Neer surukku, Neer kadupu etc. Various herbs have been mentioned in Siddha literatures for the treatment of UTI. The main aim of this review is to summarize the scientific evidences supporting the medicinal herbs mentioned in Siddha text for the treatment of UTI.